PENGARUH POLA KOMUNIKASI KELUARGA DAN POLA ASUH AUTHORITATIVE TERHADAP PERILAKU PROSOSIAL SISWA di MTs DARUSSALAM NGORO JOMBANG TAHUN PELAJARAN 2014/2015 - Muslih, Imam; Fauziyah, Nurul (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This study aims to determine the effect of the patternof family communication and parenting authoritative onprosocial behavior of students in MTs Darussalam NgoroJombang Year 2014-2015. This type of research is an ex postfacto approach to quantitative research. The technique ofcollecting data is by using questionnaires. Data analysistechnique uses the steps validity of the data, the data reliability,calculate percentages and hypothesis testing. The resultsshowed: 1) There is a very significant influence among familycommunication pattern against prosocial behavior of studentsin MTs Darussalam Ngoro Jombang Jombang. 2) There is a verysignificant influence between authoritative parenting styletoward prosocial behavior of students in MTs DarussalamNgoro Jombang. 3) There is a very significant influencebetween family communication patterns of the authoritativeparenting. 4) There is a very significant influence betweenfamily communication patterns authoritative parenting towardprosocial behavior of students in MTs Darussalam NgoroJombang. This research is expected to contribute positivelyespecially MTs Darussalam Ngoro Jombang.Keywords; Behaviors, Parenting, Authoritative, Prosocial